Espectros de raios-x em MEV indicam associação entre Al e Si em plantas acumuladoras de Al do Cerrado - Bressan, Anna Carolina Gressler [UNESP] (2014)
Aluminum (Al) accumulator plants are distributed all over the world, but in the Brazilian savanna or Cerrado there are hyper accumulator species, and some are Aldependent. We described anatomical patterns of Al storage in leaf tissues of Alaccumulators and non-accumulators using different Al-specific dyes. In addition, we measured Al-specific x-ray spectra from different regions in leaf tissues analyzed by scanning electron microscopy (SEM). Cross sections from leaves of adult plants from the Al-accumulators, Miconia albicans, M. rubiginosa (Melastomataceae), Qualea grandiflora, Q. parviflora (Vochysiaceae), and the non-accumulators Styrax ferrugineus and S. camporum (Styracaceae) were stained with hematoxylin and chrome azurol S for light microscopy. SEM analyses and x-ray spectra were used to identify sites of Al accumulation in leaves. Chrome azurol S was demonstrated to be a sharper and more contrasting Al-specific dye in relation to hematoxylin. We confirmed that the main sites for Al accumulation are cell walls of non-lignified leaf tissues of Al-accumulating plants. In these plants, we also observed Al-constitutive granules confined in cavities formed in the cortical parenchyma. The anatomical description of Al accumulation in leaves and the consistent pattern of Al association with cell walls strongly suggest structural rather than physiological roles of Al in leaves of Cerrado woody plants